2011
DOI: 10.1021/ef200107k
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Asphaltene Aggregation and Related Properties Using an Equilibrium-Based Mathematical Model

Abstract: Aggregation of asphaltenes was simulated using a mathematical model based on the following consecutive equilibrium: n A ⇄ K 1 A n and m A + A n ⇄ K 2 A n + m , where A, A n , A n+m , K 1, K 2 represent asphaltenes, n aggregates, n + m aggregates, and equilibrium constants, respectively. A mass balance lead to a n + m polynomial in C (C 0, n, m, K 1, K 2, M), where C is the concentration of free solute (monomer), M is the monomer molecular mass, and C 0 is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 22 publications
3
22
0
Order By: Relevance
“…This thermodynamics approach could be on 16 the line of that developed in Refs., 43,44 but based on the precise mechanism deduced from the MD simulations. Furthermore, the free energies of interaction necessary to the thermodynamics approach could be independently checked by MD simulations using for example umbrella sampling, as was carefully done for some asphaltene molecules and some geometries of interaction in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…This thermodynamics approach could be on 16 the line of that developed in Refs., 43,44 but based on the precise mechanism deduced from the MD simulations. Furthermore, the free energies of interaction necessary to the thermodynamics approach could be independently checked by MD simulations using for example umbrella sampling, as was carefully done for some asphaltene molecules and some geometries of interaction in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…7(a). However, 32 when different experiments made using the same sensor were compared, the repeatability was good, see 33 for example data from Sensor X, 75 days and 127 days (open squares and crosses) in Fig. 7(a).…”
Section: 5mentioning
confidence: 95%
“…It is observed that at long times there is a deviation from 32 linearity as the system approaches equilibrium. At very short times the relationship is non-linear, 33 indicating that the initial rate of adsorption is not diffusion-controlled. (Note that the chosen flow rate in 34 this work, as shown in section S.9, is sufficiently high to ensure that our adsorption process is not 35 governed by mass transport.)…”
Section: Kinetics Of Adsorption Inside a Flow Cell 26mentioning
confidence: 99%
See 2 more Smart Citations